KEJAHATAN DI BIDANG KUMPUTER “CYBERCRIME” DAN PENANGGULANGANNYA - Ruslan Abdul Gani (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
Era of globalization and information technology had an influence on the emergence of various forms of crimes that are new. The emergence of a new crime (cyber crime) is a phenomenon that requires quick and accurate response.The term cyber crime is currently refers to an act of crime associated with the virtual world (cyberspace) and crimes using computers. In general we can say the field of computer crime in general can be defined as the use of computers illegally. Or include all offenses relating to information, information system itself.